"Nunca mais a Bolívia sem os povos indígenas": a trajetória do Estado-nação ao Estado plurinacional - Janaina Ferreira da Mata (2016)
In 2009, thousand of bolivians approved in an unprecedented referendum of Constitution that deploy the Plurinational State in Bolivia, which is being considered a break with the traditional model of State-nation (exclusionary and homogenizing). It is considered a new Latin-American constitutionalism. This research analyzed the contribution of indigenous social movements to the politics transformations which led the creation of the new State model based on plurinationality and based on diversity (political, economics, legal, cultural, linguistic). In this study a descriptive survey was laid out in historical, political and social processes which led to adopt the new Constitution of 1961, 1994 and 2009. A comparative study with constitutional texts was laid out. The Plurinational State was boosted by Bolivian indigenous movement in a long process of resistance, mobilization and political confront in order to conquer their historical demands and build a proposal which it is more than constitutional recognition of ethnic and cultural diversity of Bolivia. Furthermore it incorporates the plurinationality in all state structure.